PENGARUH PERSEPSI MASYARAKAT KECAMATAN RANTAU UTARA TERHADAP MINAT MEMILIH CALON KEPALA DAERAH INDEPENDEN PADA PILKADA KABUPATEN LABUHANBATU TAHUN 2015 - Tampubolon, Daud Halomoan; Noak, Piers Andreas; Apriani, Kadek Dwita (Jurnal Nawala Politika, 2021)
The Regional Head Election of Labuhanbatu Regency is one of the forums for political participation for the public. The results of the independent candidate's vote in the Labuhanbatu Regency Election 2015 were able to compete with political party candidate. This phenomenon shows the public interest in choosing independent candidates. This research aims to determine how the effect of public perception on interest in choosing independent regional head candidate. Research method uses hypothesis test between X variable (perception) and Y variable (interest) and looks for the relationship between it. Population in research were voters in Rantau Utara District. Research used questionnaire distributed to 100 respondents who were selected through a sampling technique. Data analysis technique using cross tabulation, Pearson correlation and hypothesis test. Keyword : Independent Candidate, Perception, Interest, Political Participation